The Implementation of a Collaborative Reading Project to Foster Autonomy in Students from the Extension Course English VI at the PIA Program (2022)
ABSTRACT: This study is an action research project carried out with extension course students at PIA program from Universidad de Antioquia; a public university with its main Campus in Sevilla, Medellín. The aim of this project was to foster students’ autonomy by the implementation of a collaborative reading project. Actions consisted of the development of a reading project carried out through an organized chronogram activity. Data collection instruments included a teacher journal, a self-assessment format and one focus group interview with the learners. Findings showed that developing a collaborative reading project can be beneficial for students.